The Influences of Key Strata Compound Breakage on the Overlying Strata Movement and Strata Pressure Behavior in Fully Mechanized Caving Mining of Shallow and Extremely Thick Seams: A Case Study - Junmeng Li; Yanli Huang; Jixiong Zhang; Meng Li; Ming Qiao; Fengwan Wang (Advances in Civil Engineering)
In order to analyze the impact of compound breakage of key strata on overlying strata movement and strata pressure behavior during the fully mechanized caving mining in shallow and extremely thick seams, this paper took the 1322 fully mechanized caving face in Jindi Coal Mine in Xing County as the engineering background. Under the special mining and geological condition mentioned above, UDEC numerical simulation software was applied to research the engineering problems, and results of numerical simulation were verified through the in-site measurement. The research results showed that during the fully mechanized caving mining in shallow and extremely thick seams, the inferior key strata affected by mining movement behaved in the mode of sliding instability and could not form the stable structure of the voussoir beam after breaking and caving. In addition, the main key strata behaved in the mode of rotary instability, and the caving rocks behind the goaf were gradually compacted because of the periodic instability of the main key strata. With the continuous advance of the working face, the abutment pressure of the working face was affected by the compound breakage and periodic instability of both the inferior key strata and the main key strata, and the peaks of the abutment pressure presented small-big-small-big periodical change characteristics. Meanwhile, the risk of rib spalling ahead of the working face presented different levels of acute or slowing trends. The actual measurement results of ground pressure in the working face showed that, in the working process, the first weighting interval of the inferior key strata was about 51 m and its average periodic weighting interval was about 12.6 m, both of which were basically consistent with the results of numerical simulation. The research has great significance in providing theoretical guidance and practical experience for predicting and controlling the ground pressure under the similar mining and geological conditions.